Alien Tort Statute Litigation and Transitional Justice: Bringing the Marcos Case back to the Philippines. (12th April 2017) - Davidson, Natalie R.
Abstract ∞ : Transnational tort litigation of human rights abuses has generated an extraordinary amount of commentary. Yet there is little research on its implications for transitional justice (TJ). This article considers some of those implications through a study of a landmark case in which 10, 000 Philippine victims of torture and other abuses sued Ferdinand Marcos in US courts under the Alien Tort Statute. Analyzing Marcos from the perspective of critical approaches to TJ reveals that while victim groups used the lawsuit in empowering ways in the Philippines, their claims also conflicted with the state's transitional policy seeking economic redistribution. Ironically, enforcement difficulties mediated the conflict, leading to the enactment of a law compensating and recognizing a broader range of victims while preserving the redistribution policy. This analysis exposes some of the benefits and risks of transnational tort litigation against foreign state officials, and offers a novel perspective on the enforcement of transnational remedies for human rights violations.